2022
DOI: 10.1097/gox.0000000000004539
|View full text |Cite
|
Sign up to set email alerts
|

To Do or Not to Do? Neurorrhaphy in Great Toe Pulp Flap Fingertip Reconstruction

Abstract: Background: Since its inception, the great toe pulp (GTP) flap has represented a valid therapeutic choice in the reconstruction of defects of the hand. This study illustrates the clinical outcomes of GTP free flaps performed without nerve anastomosis‚ mainly for fingertip defect reconstruction. Methods: We performed a retrospective, monocentric cohort study. All patients included in this study presented with fingertip traumatic injury, with tendon or bone exposure; reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Many flaps involve nerves for sensory recovery, such as neurovascular island flaps, but it has been reported that sensory recovery can be achieved by non‐innervated flaps for the fingertip (Kim et al, 2013; Lee et al, 2017; Troisi et al, 2022). We performed nerve coaptation in only two cases (1 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Many flaps involve nerves for sensory recovery, such as neurovascular island flaps, but it has been reported that sensory recovery can be achieved by non‐innervated flaps for the fingertip (Kim et al, 2013; Lee et al, 2017; Troisi et al, 2022). We performed nerve coaptation in only two cases (1 and 5).…”
Section: Discussionmentioning
confidence: 99%